Causal inference between aggressive extrathyroidal extension and survival in papillary thyroid cancer: a propensity score matching and weighting analysis - Xu, Ming; Xi, Zihan; Zhao, Qiuyang; Yang, Wen; Tan, Jie; Yi, Pengfei; Zhou, Jun; Huang, Tao (Frontiers in Endocrinology, 2023)
Background: Extrathyroidal extension is a pivotal risk factor for the poor prognosis of papillary thyroid cancer. However, the effect of different extents of extrathyroidal extension on prognosis remains controversial. We performed a retrospective study to elucidate how the extent of extrathyroidal extension in papillary thyroid cancer affected the clinical prognosis of patients and its covariates. Methods: The study included 108,426 patients with papillary thyroid cancer. We categorized the extent of extension into none, capsule, strap muscles and other organs. Three causal inference methods for retrospective studies, that are: Inverse probability of treatment weighting, the Standardized mortality ratio weighting and propensity score matching analysis, were used to minimize potential selection bias. Kaplan-Meier analysis and univariate Cox regression analyses were applied to analyze the exact effect of ETE on survival in papillary thyroid cancer patients. Results: In Kaplan-Meier survival analysis, only extrathyroidal extension into or beyond the strap muscles were statistically significant for both overall survival (OS) and thyroid cancer-specific survival (TCSS). In univariate Cox regression analyses before and after matching or weighting based on causal inference, extrathyroidal extension into soft tissues or other organs are high-risk factors in both overall survival and thyroid cancer-specific survival. Sensitivity analysis revealed that lower overall survival was observed when patients with elderly age (> = 55) and larger tumor size (> 2cm) of papillary thyroid cancer with extrathyroidal extension into or beyond the strap muscles. Conclusions: Our study indicates extrathyroidal extension into soft tissues or other organs is a high-risk factor in all papillary thyroid cancer. Even though strap muscles invasion is not deemed as a marker for poor prognosis, it still impaired the overall survival of patients with elderly age (≥55 years old) or larger tumor size (>2cm). Further investigations are required to confirm our results and clarify more details regardless of extrathyroidal extension.